Production of alkaline pectinase by bacteria (Cocci sps.) isolated from decomposing fruit materials - Kumar, Ajit; Sharma, Rita (Journal of Phytology, 2012)
Bacterial production of commercial enzymes, including pectinase, has always been the industrial choice. Two decomposing fruit materials (apple and oranges) were enriched to isolate pectinase producing bacteria and were screened for their pectinolytic activity. The best producer (O1, i.e. Orange 1) was characterized as Cocci sp. and studied for pectinase activity. The culture conditions were optimized for maximum enzyme production by isolate O1 and was found to be 350C at an alkaline pH of 8.0 with 120 rpm agitation (supporting aerobic conditions) and 72 hours of incubation time and required surfactant for achieving maximum enzyme activity of 13.96 U/ml in crude enzyme extracts. The study provides a strong bacterial candidate for potential industrial production of pectinase.